2-D numerical study of ferrofluid droplet formation from microfluidic T-junction using VOSET method. (3rd May 2021) - Zhang, Shuai; Ling, Kong; Sun, Na; Yang, Siyuan; Hao, Xiangmiao; Sui, Xiaowei; Tao, Wen-Quan
Abstract: This article conducts a two-dimensional numerical model to simulate the ferrofluid droplet formation from microfluidic T-junction under inhomogeneous magnetic fields with diverse strengths. This external magnetic field is produced by two electric straight wires in a finite computational domain. A coupled volume-of-fluid and level-set interface tracking method (VOSET) is adopted to capture the evolution of two-phase interface. Meanwhile, a two-region computational domain method is designed for situations that the droplets are in close contact with the solid boundaries for the fluid flow. All 2-D numerical simulations are implemented by a self-developed CFD code, named as MHT (Multi-concept Heat Transfer). The numerical results show a significant inhibition effect in droplet formation at the presence of external magnetic field. With the increase of the current intensity, the magnetic force of the ferrofluid droplet increases and decreases periodically, especially when the electric current intensity is less than 60 A. The increasing current intensity enlarges the departure diameter and prolongs the departure period of ferrofluid droplet, especially when the current intensity in the range 12 A∼54A. In the cases of electric current within [12A, 54 A], the departure diameter growths monotonically and nearly in a quadratic manner with the increase of the current intensity. However, when the current intensity exceeds 60 A, the departure characteristic of ferrofluid will be changed due to ferrofluid droplet absorbed on the upper wall of the main channel.